Environmental evaluation of natural radioactivity in soil near a lignite-burning power plant in Turkey - Gören E.; Ş, Turhan; Kurnaz A.; Garad A.M.K.; Duran C.; Uğur F.A.; Yeğingil Z. (Elsevier BV, 2017)
Natural radionuclides are released into the environment together with fly ash from the coal-burning power plant and cause an increase in the natural radioactivity in environmental samples. The study concerns to the evaluation the influence of Kangal lignite-burning power plant (LBPP) with a power of 457 MWe, which has been in operation since 1989, on natural radionuclide a concentration in surface soil samples around it. Activity concentrations of natural radionuclides (226Ra, 232Th, 40K and 222Rn) in the soil samples, and emanation coefficient (EC) and mass (ERM) and surface (ERS) exhalation rate of radon were determined by using a gamma-ray spectrometer with an HPGe detector. The average values of 226Ra, 232Th, 40K and 222Rn, EC, ERM and ERS were found as 37±5, 17±3, 222±30Bqkg-1 and 9±1kBqm-3, 12%, 12.1 µBq kg-1 s-1 and 7.1mBqm-2 s-1, respectively. Absorbed gamma dose rate in outdoor air and the corresponding effective dose rate from external exposure and excess lifetime cancer risk were estimated to evaluate radiological hazards for human population. The results revealed that the Kangal LBPP has caused a small increment in 226Ra concentration in the studied area. No influence was observed for 232Th and 40K.
Keywords: Effective dose; Soil; Environmental radioactivity; Radon surface exhalation rate; Coal-fired power plant; Emanation coefficient; Radon mass exhalation rate; 13. Climate action